Varroa destructor parasitism and Deformed wing virus infection in honey bees are linked to peroxisome-induced pathways - Erban, Tomas; Kadleckova, Dominika; Sopko, Bruno; Harant, Karel; Talacko, Pavel; Markovic, Martin; Salakova, Martina; Kadlikova, Klara; Tachezy, Ruth; Tachezy, Jan (Proteomics, 2024)
The ectoparasitic mite Varroa destructor transmits and triggers viral infections that have deleterious effects on honey bee colonies worldwide. We performed a manipulative experiment in which worker bees collected at emergence were exposed to Varroa for 72 h, and their proteomes were compared with those of untreated control bees. Label-free quantitative proteomics identified 77 differentially expressed A. mellifera proteins (DEPs). In addition, viral proteins were identified by orthogonal analysis, and most importantly, Deformed wing virus (DWV) was found at high levels/intensity in Varroa-exposed bees. Pathway enrichment analysis suggested that the main pathways affected included peroxisomal metabolism, cyto-/exoskeleton reorganization, and cuticular proteins. Detailed examination of individual DEPs revealed that additional changes in DEPs were associated with peroxisomal function. In addition, the proteome data support the importance of TGF-β signaling in Varroa-DWV interaction and the involvement of the mTORC1 and Hippo pathways. These results suggest that the effect of DWV on bees associated with Varroa feeding results in aberrant autophagy. In particular, autophagy is selectively modulated by peroxisomes, to which the observed proteome changes strongly corresponded. This study complements previous research with different study designs and suggests the importance of the peroxisome, which plays a key role in viral infections.
Keywords: Animals; lipid metabolism; autophagy; proteom; peroxizomy; host‐pathogen interaction; Proteome; Apis mellifera; Varroidae; Host-Parasite Interactions; proteomika; interakce hostitele a parazita; signální transdukce; hmyzí proteiny; Signal Transduction; Proteomics; RNA Viruses; Bees; DWV; RNA-viry; včely; Insect Proteins; Peroxisomes; zvířata